Injectable calcium phosphate foams for the delivery of Pitavastatin as osteogenic and angiogenic agent. Issue 3 (12th June 2019) - Khurana, Kanupriya; Guillem‐Marti, Jordi; Soldera, Flavio; Mücklich, Frank; Canal, Cristina; Ginebra, Maria‐Pau
Abstract: Apatitic bone cements have been used as a clinical bone substitutes and drug delivery vehicles for therapeutic agents in orthopedic applications. This has led to their combination with different drugs with known ability to foster bone formation. Recent studies have evaluated Simvastatin for its role in enhanced bone regeneration, but its lipophilicity hampers incorporation and release to and from the bone graft. In this study, injectable calcium phosphate foams (i‐CPF) based on α‐tricalcium phosphate were loaded for the first time with Pitavastatin. The stability of the drug in different conditions relevant to this study, the effect of the drug on the i‐CPFs properties, the release profile, and the in vitro biological performance with regard to mineralization and vascularization were investigated. Pitavastatin did not cause any changes in neither the micro nor the macro structure of the i‐CPFs, which retained their biomimetic features. PITA‐loaded i‐CPFs showed a dose‐dependent drug release, with early stage release kinetics clearly affected by the evolving microstructure due to the setting of cement. in vitro studies showed dose‐dependent enhancement of mineralization and vascularization. Our findings contribute towards the design of controlled release with low drug dosing bone grafts: i‐CPFs loaded with PITA as osteogenic and angiogenic agent. Abstract :